POPULATION DYNAMICS OF BELUGAS IN KANDALAKSHSKII ZALIV (Dinamika Vstroechaemosti Belukh v Kandalakshskom Zalive) - Byanki,V. V. (1970)
The study is based on data gathered by the Kandalaksha State Sanctuary during 1947-1961. Most of the mammals were observed from islands during the navigational (free ice) period. It appears that the number of belugas that visit the gulf has greatly decreased. The greatest numbers of the mammals were observed in August-September -- a time when large concentrations of herring approach the coast. Usually, the number of belugas varies from year to year; the minimum was reached in 1948-1951 (5 in a year); the maxima in 1953 (37) and 1947 (32). (Author) Trans. of mono. Morskie Mlekopitayushchie, Moscow, 1965 p70-72, by M. Slessers.